2013
DOI: 10.1167/13.10.24
|View full text |Cite
|
Sign up to set email alerts
|

Collinear integration affects visual search at V1

Abstract: Perceptual grouping plays an indispensable role in figure-ground segregation and attention distribution. For example, a column pops out if it contains element bars orthogonal to uniformly oriented element bars. Jingling and Tseng (2013) have reported that contextual grouping in a column matters to visual search behavior: When a column is grouped into a collinear (snakelike) structure, a target positioned on it became harder to detect than on other noncollinear (ladderlike) columns. How and where perceptual gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
8
12
0
Order By: Relevance
“…In this experiment, we replicated the previous finding that search impairment was observable only with a collinear distractor equal to, or longer than, 5 elements (Chow et al, 2013) with the gradual appearance of search display.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In this experiment, we replicated the previous finding that search impairment was observable only with a collinear distractor equal to, or longer than, 5 elements (Chow et al, 2013) with the gradual appearance of search display.…”
Section: Resultssupporting
confidence: 85%
“…Collinearity as illustrated in our collinear search impairment and other studies using collinear facilitation helps address the awareness question as (1) collinear information is reported to be consistent with the dynamics of long-range horizontal interactions within primary visual cortex (V1) (Cass & Alais, 2006), and (2) collinear search impairment operates at a monocular level (Chow et al, 2013) which is again a property of V1. In Chow et al (2013), different parts of the collinear distractor were presented to different eyes through a mirror stereoscope. It was found that search impairment was determined by the monocular distractor length -search impairment was not significant if the monocular distractor was too short, even when the binocular fused length was longer than the critical length.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Not all salient items inform visual searching. Our previous studies revealed a complex interaction between salience and perceptual grouping by demonstrating that some types of salient structures hinder search (Chiu & Jingling, 2014Chow, Jingling, & Tseng, 2013Jingling, Tan, & Tseng, 2013;Jingling, Tseng, & Zhaoping, 2013;Tseng & Jingling, 2015). In these earlier studies, the search display was filled by horizontal bars, except for one salient and collinearly grouped column (Fig.…”
Section: Effect Of Visual Search Target/distractor Overlapping (1): Cmentioning
confidence: 97%
“…We recruited 20 participants, and this number was estimated from our previous studies that showed that about 10 to 15 participants were enough to obtain statistical power for our interest (Chiu & Jingling, 2014Chow et al, 2013;Jingling, Tan, & Tseng, 2013;Tseng & Jingling, 2015;Jingling, Tseng, & Zhaoping, 2013). All the participants had normal or corrected-to-normal vision according to self-reports.…”
Section: Participantsmentioning
confidence: 99%